Um estudo sobre o escoamento de um fluido newtoniano e não newtoniano através de estruturas desordenadas - Gomes, Pedro Félix Lopes (2021)
Fluid flow in porous media is a subject of intense research due to its important technological application in several processes, such as; filtration, pollutant dispersion, oil / gas extraction and catalysis. Understanding how the pore space inside the porous medium defines the way the flows are distributed during the flow is fundamental for an understanding of the processes occurring inside these structures. Experimental studies attest that, depending on the scale of the pores and the complexity of the pore networks, very heterogeneous patterns can emerge. The complexity of the pore networks that make up the porous matrix, whether ordered or disordered, greatly influences the way the flows are established within the porous environment. In this work, we propose a study on the distribution of flows within the disordered porous medium considering two flow regimes: low and high Reynolds number. The disordered porous medium is constructed by randomly allocating circular obstacles in a rectangular box until the desired porosity (empty spaces) is reached. Considering this disordered two-dimensional porous medium, we performed a series of computational experiments on the flow of a Newtonian fluid assuming different Reynolds numbers for the flow regime. We analyzed how the distribution of flows within the medium changes as a function of Reynolds for different porosities. In addition, we investigate what the effect is when the fluid considered is of the Non-Newtonian type.